Recognition of DNA three-way junctions by metallosupramolecular cylinders: gel electrophoresis studies - Malina, Jaroslav; Hannon, Michael J; Brabec, Viktor (Chemistry, 2007)
The interaction of metallosupramolecular cylinders with DNA three-way junctions has been studied by gel electrophoresis. A recent X-ray crystal structure of a palindromic oligonucleotide forming part of a complex with such a cylinder revealed binding at the heart of a three-way junction structure. The studies reported herein confirm that this is not solely an artefact of crystallisation and reveal that this is a potentially very powerful new mode of DNA recognition with wide scope. The cylinders are much more effective at stabilizing three-way junctions than simple magnesium di-cations or organic or metallo-organic tetra-cations, with the M cylinder enantiomer being more effective than P. The recognition is not restricted to three-way junctions formed from palindromic DNA with a central AT step at the junction; non-palindromic three-way junctions and those with GC steps are also stabilised. The cylinder is also revealed to stabilise other Y-shaped junctions, such as that formed at a fraying point in duplex DNA (for example, a replication fork), and other DNA three-way junction structures, such as those containing unpaired nucleotides, perhaps by opening up this structure to access the central cavity.
Keywords: financování organizované; Electrophoresis, Polyacrylamide Gel; Base Sequence; Metals; DNA; spektrofotometrie ultrafialová; Nucleic Acid Conformation; Stereoisomerism; stereoizomerie; kovy; krystalografie rentgenová; konformace nukleové kyseliny; Financing, Organized; Models, Molecular; molekulární modely; Spectrophotometry, Ultraviolet; sekvence nukleotidů; Crystallography, X-Ray; elektroforéza v polyakrylamidovém gelu